Effect of Acids on Biomass Growth and Development of Chlorella vulgaris Culture - Alona Vdovychenko; Nataliia Golub; Marcin Zieliński; Igor Levtun (Innovative Biosystems and Bioengineering)
Background. Influence of dissolved nitrogen and sulfur oxides, as components of flue gases, on the cultivation of microalgae Chlorella vulgaris.